Effects and outcome of Direct Acting Antiviral Therapy for Eradication of Hepatitis C in Kidney Transplant patients - Ahmed Ayyaz, Azhar Ali Khan, Nasir Ibrahim, Sehrish Sarwar, Azhar Waheed Khan, Hafiz Hamad Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To look for effects and graft outcome of Direct Antiviral Agents on Hepatitis C positive Renal Transplant Patients Design: Prospective study Duration & place of study: The study will be conducted in Shaikh Zayed Hospital’s Kidney Transplant Unit, Lahore, and will comprises of consecutive Hepatitis C positive Renal Transplant Recipients from January 2018 to January 2020 Methodology: The Hepatitis C Positive Renal Transplant Recipients will be selected after fulfilling Inclusion and Exclusion Criteria and we will follow the patient for 3 months after initiation of DAA regime. Result: The study included 50 patients average age was 36.1±10.5 years and 32(64%) of them were male and rest were females. Therapy for HCV was 100.0% successful. The total bilirubin levels, hemoglobin, platelet count, serum creatinine and eGFR had no significant change in averages over 12 weeks of treatment. The ALT and AST levels reduced significantly in first 4-week time and then stayed at a level while the ALP levels reduced significantly over all intervals of follow-ups. The albumin levels increased significantly at week 8 and stayed unchanged on week 12 as compared to baseline. The WBC count and blood glucose levels reduced significantly from baseline till end of study. 12th week was compared with baseline, it was observed that among 29 with eGFR >90 at baseline 7(24.1%) had eGFR 60 – 90 and 3(10.3%) had eGFR even less (30 – 60). Conclusion: HCV is a well-recognised risk factor of poor graft survival in kidney transplant patients. In our study it was observed that DAA treatment can resolved HCV infection in kidney Transplant Recipients with significant improvement of liver function without loss of allograft function.